Independent and Opposing Associations of Habitual Exercise and Chronic PM2.5 Exposures on Hypertension Incidence. Issue 7 (18th August 2020) - Guo, Cui; Zeng, Yiqian; Chang, Ly-yun; Yu, Zengli; Bo, Yacong; Lin, Changqing; Lau, Alexis KH; Tam, Tony; Lao, Xiang Qian
Abstract : Background: We investigated the joint associations of habitual physical activity (PA) and long-term exposure to fine particulate matter (PM2.5 ) with the development of hypertension in a longitudinal cohort in Taiwan. Methods: We selected 140 072 adults (≥18 years of age) without hypertension who joined a standard medical screening program with 360 905 medical examinations between 2001 and 2016. PM2.5 exposure was estimated at each participant's address using a satellite data-based spatiotemporal model with 1 km 2 resolution. Information on habitual PA and a wide range of covariates was collected using a standard self-administered questionnaire. We used the Cox regression model with time-dependent covariates to examine the joint associations. Results: The mean age of all observations was 41.7 years, and 48.8% were male. The mean value for systolic and diastolic blood pressure was 112.5 and 68.7mm Hg, respectively. Approximately 34.2% of all observations were inactive (0 metabolic equivalence values-hours), 29.8% had moderate-PA (median [interquartile range]; 3.75 [3.38 to 4.38] metabolic equivalence values-hours), and 36.0% had high-PA (15.7 [10.3 to 24.8] metabolic equivalence values-hours). The mean±SD of PM2.5 was 26.1±7.3 μg/m 3 . The prevalence of cardiovascular disease, diabetes mellitus, and cancer was 2.1%, 2.9%, and 1.5%, respectively. After adjusting for a wide range of covariates (including a mutual adjustment for PA or PM2.5 ), a higher PA level was associated with a lower risk of hypertension (hazard ratio [HR] for the moderate- and high-PA was 0.93 [95% CI, 0.89–0.97] and 0.92 [95% CI, 0.88–0.96], respectively, as compared with the inactive-PA), whereas a higher level of PM2.5 was associated with a higher risk of hypertension (HR for the moderate- and high-PM2.5 was 1.37 [95% CI, 1.32–1.43] and 1.92 [95% CI, 1.81–2.04], respectively, as compared with the low-PM2.5 group]. No significant interaction was observed between PA and PM2.5 (HR 1.01 [95% CI, 1.00–1.02]). Conclusions: A high-PA and low PM2.5 exposure were associated with a lower risk of hypertension. The negative association between PA and hypertension remained stable in people exposed to various levels of PM2.5, and the positive association between PM2.5 and hypertension was not modified by PA. Our results indicated that PA is a suitable hypertension prevention strategy for people residing in relatively polluted regions. Abstract : Supplemental Digital Content is available in the text.